In the Heat of the Short-Term Moment: Evidence that Heightened Sexual Arousal Increases Short-Term Mating Motivation Among Men - Andrew Thomas (Evolutionary Psychological Science, 2022)
Individual differences in men’s short-term mating interest are well studied, both at state and trait levels. Yet, the role of sexual arousal as a source of intra-individual variation has been neglected. This research represents the first attempt to integrate sexual arousal into the human mate plasticity literature. We argue that sexual arousal directly impacts the short-term mating motivation among men regardless of their personality, relationship status, and sociosexuality. Across four experiments, we found that heightened sexual arousal consistently increased men’s short-term mating motivation relative to participants in neutral and arousing control groups. Experiments 1 and 2 revealed that sexual arousal increased participants’ general short-term mating motivation and their preference for a short-term relationship over a long-term one. Experiment 3 replicated the findings of the first two experiments whilst also demonstrating that this effect was not moderated by personality (i.e., Dark Triad, Big Five) or relationship status. Heightened sexual arousal also led to decreased “state” long-term mating motivation. Finally, Experiment 4 showed that sexual arousal increased the participants’ preference for a short-term relationship over a long-term one, an effect that was not moderated by sociosexuality. Together, the results suggest that sexual arousal has a powerful effect on men’s short-term mating motivation, and that this effect is independent of intrasexual differences in personality, relationship status, and sociosexuality.